Zaključna publikacija Urban Diversity - Beznec, Barbara; Gombač, Jure; Kastelic, Špela (ZRC SAZU, Založba ZRC, 2020)
The Urban Diversity Final Publication is a representation of Urban Diversity project that lasted between 2017 and 2020. The project's aim was a creative connection of migrant entrepreneurs and their families in Ljubljana and Graz, and to help encourage and promote diversity in both cities. There are already some support and aid programs for self-employment and business establishment for migrants, however both cities also trace obstacles that abate migrant entrepreneurs from being creative and integrate into the society. These obstacles can be found on different levels, and are not easy to define or remove, while they also represent a large issue for migrant entrepreneurs and the host society, which stuns their potential and its own economic and social progress. The results and achievements in the publication present the good practice of removing social obstacles that already exist elsewhere in Europe.